ENTERPRISE RISK MANAGEMENT DAN KUALITAS LABA: PERAN DARI KOMPETENSI AUDIT INTERNAL - Budi Kurniawan; Donant Alananto Iskandar; Basuki Toto Rahmanto (Universitas Multimedia Nusantara, 2023)
Abstract - There is debate whether ERM can improve the quality of financial reporting information or not. This study aims to examine the effect of the level of ERM disclosure on the quality of company earnings which is then moderated by internal audit competence. The sample of this study are companies listed on the Indonesia Stock Exchange during 2019 except for financial sector companies. The results of this study show that the level of ERM disclosure has no effect on earnings predictability, earnings smoothing, and earnings volatility. In addition, internal audit competency moderation does not affect the relationship between the level of ERM implementation and earnings quality as measured by earnings predictability, earnings smoothing, and earnings volatility. The implication of this research is that stricter policies will encourage companies to implement ERM better. Future research can test the level of ERM implementation using a case study approach. Keywords: Enterprise Risk Management; Implementasi ERM; Kualitas Laba; Earnings Predictability; Earnings Smoothing; Earnings Volatility; Kompetensi Audit Internal.